Robust assessment of external vulnerabilities in an emerging market during stress scenarios - Diego Alejandro Martínez Cruz; Philip Rory Symington Alzate (Graduate Institute of International and Development Studies, 2024)
Foreign portfolio flows constitute a key component of economic activity in small open economies such as Colombia. The dynamics of these flows are subject to the influence of both external (push) factors and domestic (pull) factors. Consequently, economic crises and episodes of financial distress can severely undermine investor confidence, leading to a sharp decline in foreign capital inflows and the subsequent liquidation of local assets, commonly referred to as a sudden stop and sudden start. Such events can have lasting adverse effects on various facets of the economy, including GDP growth, employment rates, financial stability, and investor sentiment. This paper delves into the dynamics of portfolio external investment and which factors can explain them on major Latin American economies and quantifies the potential reduction in foreign investors' holdings of local assets under high external risk scenarios. For the Colombian case, we estimate a potential liquidation of 43.8% of total foreign investors portfolio under the most severe assumed scenario. Our work provides insights to be integrated into various exercises aimed at formulating precautionary policy measures, such as those entailed in the evaluation of adjustments to foreign exchange reserves and other external buffers by the central banks.
Keywords: F21; F31; F32; F34; G15; G17; E44; 330; Foreign Portfolio Flows; Small Open Economies; Economic Crises; Sudden Stop; Sudden Start; Financial Distress; Pull Factors; Push Factors